Management of Valsa Canker on Apple with Adjustments to Potassium Nutrition - Peng, H X (Plant disease, 2016)
Valsa canker, caused by the fungus Valsa mali, is one of the most destructive diseases of apple in the primary production areas of China and other East Asian countries. Currently, there are no effective control methods for this disease. We investigated the occurrence of Valsa canker in 24 apple orchards in Shaanxi Province in concert with foliar nutrient analysis, and found that there was a significant negative correlation of leaf potassium (K) content with incidence and severity of Valsa canker. Fertilization experiments showed that increasing tree K content enhanced resistance to pathogen colonization and establishment. Apple trees with leaf K content greater than 1.30% exhibited almost complete resistance to Valsa mali. Field trials demonstrated that increasing K fertilization could significantly reduce disease incidence. Improved management of tree nutrition, especially K content, could effectively control the occurrence and development of Valsa canker